Semantic Properties of Anthroponyms - Nazarova Navbahor Ahrorovna (Indonesian Journal of Innovation Studies, 2022)
This article discusses the lexical-semantic features of anthroponyms, their origin and etymology as well. Anthroponyms have also been analyzed on the example of some names.